Peptidylarginine deiminase 4 concentration, but not PADI4 polymorphisms, is associated with ICU mortality in septic shock patients - Costa, Nara Aline [UNESP]; Gut, Ana Lúcia [UNESP]; Azevedo, Paula Schmidt [UNESP]; Polegato, Bertha Furlan [UNESP]; Magalhães, Eloá Siqueira [UNESP]; Ishikawa, Larissa Lumi Watanabe [UNESP]; Bruder, Rita de Cassia Siqueira [UNESP]; Silva, Evelyn Aparecida da [UNESP]; Gonçalves, Renan Braga [UNESP]; Tanni, Suzana Erico [UNESP]; Rogero, Marcelo Macedo; Norde, Marina Maintinguer; et al. (Wiley, 2018)
The objective of our study was to evaluate the association between peptidylarginine deiminase 4 (PAD4) concentration and its polymorphisms with mortality in patients with septic shock. We prospectively evaluated 175 patients aged over 18 years with septic shock upon intensive care unit (ICU) admission. However, 48 patients were excluded. Thus, 127 patients were enrolled in the study. At the time of the patients’ enrollment, demographic information was recorded. Blood samples were taken within the first 24 hours of the patient’s admission to determine serum PAD4 concentrations and its polymorphism PADI4_89 [rs11203366], PADI4_94 [rs2240340] and PADI4_104 [rs1748033]. The mean age was 63.3 ± 15.2 years, 56.7% were male, PAD4 concentration was 4.62 (2.48-6.20) ng/mL and the ICU mortality rate was 67.7%. The patients who died in the ICU had higher APACHE II and Sequential Organ Failure Assessment (SOFA) scores. In addition, PAD4 concentration was higher in patients who died during ICU stay. However, there were no differences regarding PADI4 polymorphisms and ICU mortality. In the logistic regression models, PAD4 concentrations were associated with ICU mortality when adjusted for APACHE II score and lactate (OR: 1.477; CI 95%: 1.186-1.839; P <.001), and when adjusted for age, gender and APACHE II score (OR: 1.392; CI 95%: 1.145-1.692; P <.001). In conclusion, PAD4 concentration, but not PADI4_89, PADI4_94 and PADI4_104 polymorphisms, is associated with ICU mortality in septic shock patients.
Keywords: Citrullination; Neutrophils extracellular traps; Peptidylarginine deiminase 4; Sepsis; Single nucleotide polymorphisms